2006
DOI: 10.1016/j.ccr.2005.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature lifetimes of metastable high-spin states in spin-crossover and in low-spin iron(II) compounds: The rule and exceptions to the rule

Abstract: The high-spin → low-spin relaxation in spin-crossover compounds can be described as non-adiabatic multi-phonon process in the strong coupling limit, in which the low-temperature tunnelling rate increases exponentially with the zero-point energy difference between the two states. Based on the hypothesis that the experimental bond length difference between the high-spin and the low-spin state of not, vert, similar0.2 Å is also valid for low-spin iron(II) complexes, extrapolation of the single configurational coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
255
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(273 citation statements)
references
References 54 publications
10
255
0
Order By: Relevance
“…[7] Another important area of SCO research concerns light-induced excited-spin-state trapping (LIESST). [3,8,9] The metastable HS state can be very long-lived if the temperature is kept low enough, and many Fe II systems display LIESST.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Another important area of SCO research concerns light-induced excited-spin-state trapping (LIESST). [3,8,9] The metastable HS state can be very long-lived if the temperature is kept low enough, and many Fe II systems display LIESST.…”
Section: Introductionmentioning
confidence: 99%
“…So, if in the warped surface depicted in Figure 1, the minima describe an elongated conformation and the saddle points correspond to a compressed one, B > 0, while the reverse happens if B < 0. Accordingly, if B > 0, the electronic ground state is B 1g for a d 9 ion and A 1g for a d 7 ion. Furthermore, in a static JT effect, the barrier controls the rate of incoherent transitions among the three wells and thus the passage of a tetragonal EPR spectrum to an isotropic one when the temperature is raised.…”
Section: Introductionmentioning
confidence: 99%
“…However, although they perform quite well for the study of numerous properties of transition metal complexes, 59 they tend to dramatically fail when it comes to the accurate evaluation of the relative energies of the different spin-states of these systems. 6,7,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] [L], respectively, where r Γ designates the average iron-nitrogen bond length in the Γ manifold (Γ ) LS, HS).…”
Section: +mentioning
confidence: 99%
“…The quantitative analysis of the low-temperature relaxation dynamics reported for [Fe(bpy) 3 ] 2+ within this framework showed that the different environments provided by these hosts make ∆E HL°v ary between 2500 and 5000 cm -1 . 6,7 In passing from the LS to the HS state, the metal-ligand bond length of [Fe(bpy) 3 ] 2+ increases by ∆r HL ) r HS -r LS ≈ 0.2 Å, and concomitantly, the molecular volume increases by ∆V HL ) V HS -V LS ≈ 20 Å 3 . 6,8 This is caused by the promotion of two electrons from the metallic nonbonding orbital levels of octahedral t 2g parentage into the antibonding ones of e g parentage.…”
Section: Introductionmentioning
confidence: 99%